Research of energy-saving air distribution unit of a perforator - Alkon Glazov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is caused by the need to develop a pneumatic perforator with low airflow. The aim of the research is to study the regularities of the distribution device operation and data obtain to develop energy-saving design of the perforator with low airflow. Research methods: experimental strain gauge instrumentation with sensors and air mass flow. The data were computer analyzed. Results. The paper introduces the results of experimental studies of the new hammer mechanism with two standalone distribution valve bodies of the pneumatic rock drill PC-75M. It has been affirmed that the use of a single distribution body in the shocking mechanism does not allow implementing a cost effective cycle of the mechanism operation. By the example of this device, the author substantiates the idea that the use of switchgear distribution with two bodies, managing separately by the working chambers, can significantly reduce air consumption. The paper describes the impactor core drill construction and the switchboard operation. The influence of the mass, size and stroke of the distribution bodies on the workflows in the chambers and the switchgear operation was studied. The author obtained the dependences of energy, power and time characteristics of the impact mechanism and its elements and identified the areas of the valves stable operation. It is shown that working chambers were cut-off from the network in the shocking mechanism by the moment of the exhaust windows opening. The author worked out the proposals on further increase of the hammer mechanism performance and defined the flow characteristics in the section of the intake line of the forward stroke chamber. The paper shows the nature of the processes occurring in the command channel. The influence of the command channel area on energy and power characteristics of the mechanism and the switchgear operation was studied experimentally. The authors studied as well the influence of the inlet channels area of the reverse camera on the hammer mechanism operation. The airflow of the new mechanism was 3,8 m3 /min, the total noise of the rock drill PC-75M is 8-10 dB lower than that of the rock drill PC-75.